Modules de Formation: Changement cliamtique et Agriculture Climato- intelligente: concepts et outils - Ouedraogo, Mathieu (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Modules delivered in French, to the 20 SMEs enrolled in the Gender Accelerator Challenge program during the 2 days trianing on Climate Smart Agriculture (CSA) and Climate Information Services (CIS) held in Dakar, in October 25-26th 2022.